Promotional Strategy of Dinas Koperasi dan UKM DIY in Increasing the Number of Tourists in Teras Malioboro 1 by 2023 - Allfa Rian Chaniago; Sovia Sitta Sari (Jogjakarta Communication Conference (JCC), 2024)
This study aims to describe the promotional strategy employed by the Dinas Koperasi dan UKM DIY to increase the number of tourists visiting Teras Malioboro 1 in 2023. Specifically, it investigates the application of the promotion mix, the utilization of digital media for promotional activities, and examines consumer responses related to the promotional strategies implemented by the Dinas Koperasi dan UKM DIY as the manager of Teras Malioboro 1. The research method utilized in this study is descriptive qualitative analysis. Data for this research were gathered through documentation review and in-depth interviews with key informants from the relevant field or department within the organizational structure of the Dinas Koperasi dan UKM DIY responsible for managing Teras Malioboro 1. The collection of data involved conducting thorough interviews and reviewing pertinent documentation with informants from the Dinas Koperasi dan UKM DIY, as well as with visitors to Teras Malioboro 1. The findings of this study indicate that the Dinas Koperasi dan UKM DIY has set the objective of promotional activities to increase tourist visits to Teras Malioboro 1. Furthermore, the study identifies the promotion mix employed and the media channels utilized for disseminating promotional messages.